"Rød og hvid i Billedsalen". Grundtvigs døds- og mindedigte II - Lundgreen-Nielsen, Flemming (Grundtvig-studier, 1981)
"Red and White in the Picture Gallery” Grundtvig’s memorial poems (II)By Flemming Lundgreen-Nielsen In the second and last part o f the essay three memorial poems from the 1840’s are considered in order o f their publication. “ Henrich Steffens” (1845) is Grundtvig’s final appraisal o f his cousin for his role as herald o f Danish romanticism. At the end Grundtvig even suggests Steffens’ grave be moved from Berlin to Sorø Academy, the site o f Grundtvig’s proposed folk highschool, since Steffens may be declared the real father o f the popular enlightenment to come. Grundtvig probably got the idea from the tomb for Thorvaldsen in the court-yard o f the sculptor’s museum in Copenhagen. “ Albert Thorvaldsen” (1844, printed 1848) was thus written partly to argue against the official funeral speeches at the state funeral in 1844. Grundtvig categorizes Thorvaldsen as a “ Lysalf” (fairy o f the light), i.e. a pagan with reverence for spirit, but not a Christian believer. “ Povel Dons” (1843, printed 1867) describes the sad career o f a broken man whose ambitions far surpassed his talents. With a daring quote from Christ Grundtvig resurrects him to an after-life as faithful helper o f the Danish romantics. It is demonstrated that the close parallels between the Greek myths o f Icaros and Phaeton and Nordic mythology and Lutheran Easter metaphors have produced one o f Grundtvig’s most condensed and successful lyrical texts.In conclusion it is emphasized that Grundtvig’s hallmark as a memorial poet neither concerns details from the private existence nor an appreciation of the works o f the deceased person, but that Grundtvig boldly interprets his or her function in universal and national spiritual history. In his best memorial poems Grundtvig hardly offers Christian consolation, he rather adheres to a semi-pagan reincarnation o f the spirit-formula, as seen in Jens Baggesen’s epic “ Thora from Havsgaard” and in Grundtvig’s own interpretations o f the myth about Balder’s Death and Funeral. To Grundtvig the memorial poem is mainly a secular literary genre.